Pollen Grains in the Genetic Improvement of Trees - Sharma, C. M. (Indian Forester, 1992)
The inheritance pattern of the trees is still incompletely known, therefore, more practical aspects for the tree genetic improvement and breeding programmes should be undertaken to obtain genetically better trees. The study of pollen physiology is engaging considerable attention in tree improvement programmes. The germination of pollen grains both in-vivo and in-vitro, pollen viability and longevity including storage, selective and controlled pollination, sterility, its applications and incompatibility, pollen chemistry and energy contents, irradiation, crossability patterns are, therefore, discussed briefly to understand the role of pollen grains in tree genetic improvement processes.